2008
DOI: 10.1002/cb.244
|View full text |Cite
|
Sign up to set email alerts
|

Societal and individualistic drivers as predictors of organic purchasing revealed through a portrait value questionnaire (PVQ)‐based inventory

Abstract: The Schwartz's Portrait Value Questionnaire (PVQ) has extensively been used in personal values research. The present survey validates and tests in a value-based segmentation task a 17-item PVQ-based inventory that includes consumer values related to organic food purchasing, using a nationally representative sample of 1043 Greek consumers. The main assumption of the survey is that consumer segments that place more emphasis on specific organic food-related values would present different magnitude of beliefs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 58 publications
8
80
0
8
Order By: Relevance
“…In addition, more tradition-oriented consumers might perceive the status quo as sustainable enough and, thus, show a lower WTP for the tested sustainability attributes. The frequent presence of consumers showing high "universalism nature" values in the "medium WTP" and "high WTP" cluster are in line with studies from other study areas, which show that the value "universalism nature" is related to a more sustainable consumption behavior (De Boer et al, 2007;Krystallis et al, 2008;Thøgersen & Ölander, 2002). The negative probability of consumers attaching high importance to the "benevolence Caring" value in the "medium WTP" cluster is surprising and difficult to interpret: it indicates that consumers with high scores on the "benevolence caring" value, can be found more frequently in the "no WTP" or in the "high WTP" cluster.…”
Section: Wtp In Different Consumer Segmentssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, more tradition-oriented consumers might perceive the status quo as sustainable enough and, thus, show a lower WTP for the tested sustainability attributes. The frequent presence of consumers showing high "universalism nature" values in the "medium WTP" and "high WTP" cluster are in line with studies from other study areas, which show that the value "universalism nature" is related to a more sustainable consumption behavior (De Boer et al, 2007;Krystallis et al, 2008;Thøgersen & Ölander, 2002). The negative probability of consumers attaching high importance to the "benevolence Caring" value in the "medium WTP" cluster is surprising and difficult to interpret: it indicates that consumers with high scores on the "benevolence caring" value, can be found more frequently in the "no WTP" or in the "high WTP" cluster.…”
Section: Wtp In Different Consumer Segmentssupporting
confidence: 86%
“…Several studies have shown that, in particular, "universalism-nature," but also "benevolence-caring," are related to a more sustainable consumption behavior (De Boer, Hoogland, & Boersema, 2007;Krystallis, Vassallo, Chryssohoidis, & Perrea, 2008;Thøgersen & Ölander, 2002). These two values are closest to the social and ecological dimensions of sustainability and, hence, were included in this research.…”
Section: Measuring Values Knowledge Involvement and Perceived Consmentioning
confidence: 99%
“…Results were used to verify two assumptions, based largely on previous studies on the value antecedents of (self-reported) proenvironmental behaviour (cf. Grunert and Jørn Juhl, 1995;Gutierrez Karp, 1996;Krystallis et al, 2008;Pepper et al, 2009;Shaw et al, 2005;Stern and Dietz, 1994;Thøgersen and € Olander, 2002): a) Consumers engaging in collaborative consumption score higher on self-transcendence values (and, in particular, universalism) and openness to change values. b) Consumers engaging in collaborative consumption score lower on self-enhancement and conservation values.…”
Section: Quantitative Data Collection and Analysismentioning
confidence: 99%
“…Previous studies highlight the importance of price perception in determining consumers' attitudes towards organic foods and their organic food purchase intentions (Magnusson, Arvola, Koivisto Hursti, Aberg, & Sjödén, 2001;Fotopoulos & Krystallis, 2002;Vindigni, Janssen, & Jager, 2002;Lea & Worsley, 2005;Padel & Foster, 2005;Krystallis, Vassallo, Chryssohoidis, & Perrea, 2008).…”
Section: Organic Food Consumption Motivesmentioning
confidence: 99%